2009
DOI: 10.1007/s10801-009-0173-4
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic Gröbner bases for smooth 3×3 transportation polytopes

Abstract: Abstract. The toric ideals of 3 × 3 transportation polytopes T rc are quadratically generated. The only exception is the Birkhoff polytope B 3 .If T rc is not a multiple of B 3 , these ideals even have squarefree quadratic initial ideals. This class contains all smooth 3 × 3 transportation polytopes.1. IntroductionIf X P is smooth (the normal fan of P is unimodular), then L P is very ample, and provides an embedding X P ֒→ P r−1 , where r = #(P ∩ d ). So we can think of X P as canonically sitting in projective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 9 publications
2
27
0
Order By: Relevance
“…However, as noted by Haase and Paffenholz [HP09], for n = 3, the polytope B 3 corresponds to an embedding of X(Σ 3 ) as the cubic hypersurface x 0 x 1 x 2 = x 3 x 4 x 5 in the projective space P 5 . Since the homogeneous ideal of this embedding is not generated by quadrics, it follows that X × X × X has no splitting compatible with (∆ × X) ∪ (X × ∆).…”
Section: Compatibly Split Subdiagonalsmentioning
confidence: 91%
“…However, as noted by Haase and Paffenholz [HP09], for n = 3, the polytope B 3 corresponds to an embedding of X(Σ 3 ) as the cubic hypersurface x 0 x 1 x 2 = x 3 x 4 x 5 in the projective space P 5 . Since the homogeneous ideal of this embedding is not generated by quadrics, it follows that X × X × X has no splitting compatible with (∆ × X) ∪ (X × ∆).…”
Section: Compatibly Split Subdiagonalsmentioning
confidence: 91%
“…More importantly to each projective toric quiver variety there are an infinite number of quiver polytopes associated, hence there did not seem to be any obvious way to achieve our goal via direct computation. Instead we follow an approach similar to that of [16], where it was shown that amongst the 3 × 3 transportation polytopes, only the Birkhoff polytope B 3 yields a toric ideal which is not generated in degree two. This is a special case of our result, since 3 × 3 transportation polytopes are quiver polytopes of the bipartite quiver K 3,3 .…”
Section: G G *mentioning
confidence: 99%
“…The aim of our work in Section 4 is to refine this result by listing the quiver polytopes up to a fixed dimension that yield a toric ideal that can not be generated in degree two. One of the key tools we use here is a hyperplane subdivision method which was also applied in [16] to study the toric ideals of 3 × 3 transportation polytopes. This method allows us to estimate the generators of the toric ideals of quiver polytopes by finding generators for some small subpolytopes which we call quiver cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One important property of this method of refinement is that pulling a vertex preserves regularity of the subdivision: If C is a regular subdivision of a polytope P and C is a pulling refinement of C, then C is a regular subdivision of P . See [14,20]. A lattice polytope P such that all pulling triangulations of P are unimodular is called compressed.…”
Section: All That We Have Left To Show Is Property (D)mentioning
confidence: 99%